METHODOLOGICAL BACKGROUND FOR DEVELOPMENT OF A SYSTEM OF GROWTH AND PRODUCTIVITY MODELS FOR STANDS OF THE MAIN FOREST-FORMING TREE SPECIES OF UKRAINE - Lakyda, І. P.; Vasylyshyn, R. D. (Forestry and Forest Melioration, 2018)
Introduction During a prolonged period of forest management, scientific research and practice of forestry have accumulated a substantial amount of regulatory and information support, which is actively used for describing dynamics of forest stands when carrying out forest inventory and planning activities. The distinctive feature of the current circumstances for forestry branch is the impossibility of trustworthy application of the existing description of forests’ growth and productivity patterns under climate change conditions and variability of other environmental factors. Accounting for an influence of climatic changes on growth and bioproductivity of Ukrainian forests implies fulfillment of a series of stages towards systematization and improvement of the existing forestry-related regulatory and information support, and its embedding into one or several existing global or regional models of forest ecosystems dynamics. The main research aim is to develop a unified system of growth and productivity models for stands of the main forest-forming tree species of Ukraine. Materials and Methods A number of growth and yield tables of modal stands of the major forest-forming tree species, developed by different authors, were identified as an input data. The methodological ground is formed by the developments of Ecosystems Services and Management Program of the International Institute for Applied Systems Analysis in modeling growth, productivity and bioproductivity of forests. The following mensurational indices from growth and yield tables were taken as primary ones for further modeling: mean stand height, mean stand diameter, stand basal area, growing stock, and total productivity. The rest of mensurational indices, which traditionally are included into growth and yield tables, could be taken as derivative ones, since they may be calculated based on the well-known “classic” formulas of forest mensuration. Von Bertalanffy’s growth function serves as a mathematical basis for the research, by means of which fitting of series of dynamics of stand mean height, diameter, basal area sum, growing stock and total productivity was secured for the studied stands. Results and Conclusions The fundamental prerequisites for creating the system of growth and productivity models for stands of the main forest-forming tree species of Ukraine on basis of the yield tables proposed by Ukrainian scientists and ways for its further development and improvement are grounded. A system of growth and productivity models for modal stands of the main forest-forming tree species of Ukraine was developed. Application of approbated and internationally recognized and harmonized approaches during its development enables enhancing of the system in the future for better capturing of regional peculiarities of forest stands dynamics and supplementing it with growth models of fully-stocked stands, which are actively used in the practice of forest management and planning. The scientific research creates preconditions for forecasting growth and productivity of forests in Ukraine under the climate change conditions by means of internationally approbated and recognized regional and global models of forest ecosystems dynamics.